Patient-reported outcomes with first-line durvalumab plus platinum-etoposide versus platinum-etoposide in extensive-stage small-cell lung cancer (CASPIAN): a randomized, controlled, open-label, phase III study. (November 2020) - Goldman, Jonathan W.; Garassino, Marina Chiara; Chen, Yuanbin; Özgüroğlu, Mustafa; Dvorkin, Mikhail; Trukhin, Dmytro; Statsenko, Galina; Hotta, Katsuyuki; Ji, Jun Ho; Hochmair, Maximilian J.; Voitko, Oleksandr; Havel, Libor; et al.
Highlights: In CASPIAN, first-line durvalumab + EP improved OS vs EP in patients with ES-SCLC. Patient-reported outcomes (PROs) were prespecified secondary endpoints. Symptom burden was reduced in both arms over 12 months or until progression. Durvalumab + EP delayed worsening of symptoms, functioning, and QoL vs EP. Addition of durvalumab to EP had no additional detrimental impact on PROs. Abstract: Objectives: In the phase III CASPIAN study, first-line durvalumab plus etoposide in combination with either cisplatin or carboplatin (EP) significantly improved overall survival (primary endpoint) versus EP alone in patients with extensive-stage small-cell lung cancer (ES-SCLC) at the interim analysis. Here we report patient-reported outcomes (PROs). Materials and methods: Treatment-naïve patients with ES-SCLC received 4 cycles of durvalumab plus EP every 3 weeks followed by maintenance durvalumab every 4 weeks until progression, or up to 6 cycles of EP every 3 weeks. PROs, assessed with the European Organisation for Research and Treatment of Cancer (EORTC) Quality of Life Questionnaire-Core 30 (QLQ-C30) version 3 and its lung cancer module, the Quality of Life Questionnaire-Lung Cancer 13 (QLQ-LC13), were prespecified secondary endpoints. Changes from baseline to disease progression or 12 months in prespecified key disease-related symptoms (cough, dyspnea, chest pain, fatigue, appetite loss) were analyzed with a mixed model for repeated measures. Time to deterioration (TTD) of symptoms, functioning, and global health status/quality of life (QoL) from randomization was analyzed. Results: In the durvalumab plus EP and EP arms, 261 and 260 patients were PRO-evaluable. Patients in both arms experienced numerically reduced symptom burden over 12 months or until progression for key symptoms. For the improvements from baseline in appetite loss, the between-arm difference was statistically significant, favoring durvalumab plus EP (difference, −4.5; 99% CI: −9.04, −0.04; nominal p = 0.009). Patients experienced longer TTD with durvalumab plus EP versus EP for all symptoms (hazard ratio [95% CI] for key symptoms: cough 0.78 [0.600‒1.026]; dyspnea 0.79 [0.625‒1.006]; chest pain 0.76 [0.575‒0.996]; fatigue 0.82 [0.653‒1.027]; appetite loss 0.70 [0.542‒0.899]), functioning, and global health status/QoL. Conclusion: Addition of durvalumab to first-line EP maintained QoL and delayed worsening of patient-reported symptoms, functioning, and global health status/QoL compared with EP.